Hubungan Pendapatan dan Status Ketahanan Pangan Rumah Tangga di Wilayah Pesisir di Kecamatan Sidoarjo Kabupaten Sidoarjo (Studi Penelitian di Dusun Kalikajang Kelurahan Gebang) - Aisyah Fitria Susanti (Universitas Airlangga, Kampus C, Mulyorejo, Surabaya-60115, East Java, Indonesia, 2019)
Background: Household food security in coastal areas can be seen from indicators of availability, access, food utilization and stability. One of the pillars of house hold food security can be influenced by household income.Objective: This study aimed to analyze the relationship between the level of household income and the status of household food security in isolated coastal areas in Kalikajang Hamlet, Gebang Sub-District, District of Sidoarjo, Sidoarjo Regency.Method: This type of research was observational study with cross sectional design. The population in this study were all households in the area of Kalikajang Hamlet, Sub-District of Gebang. Sample was determined using simple random sampling technique and using formula from Lemeshow, resulted in 52 respondents included in this study. Primary data was collected through interviews with questionnaires. Data analysis using Chi Square statistical test to test the relationship between independent variables and dependent variables, and logistic regression tests to test whether there is a relationship between all independent variables with the dependent variable.Results: The results of the study showed that from the eight of independent variables tested, there was one variable that was positively related to the level of household food security, namely household income (p-value<0.001).Conclusion: There is a significant relationship between the level of income and the status of household food security in coastal areas in the District of Sidoarjo.ABSTRAKLatar Belakang: Ketahanan pangan rumah tangga di wilayah pesisir dapat dilihat dari indikator ketersediaan, akses, pemanfaatan pangan dan stabilitas. Salah satu pilar yang mempengaruhi adalah pendapatan rumah tangga.Tujuan: Penelitian ini bertujuan untuk menganalisis hubungan antara tingkat pendapatan rumah tangga dengan status ketahanan pangan rumah tangga di wilayah pesisir tambak terisolir di Dusun Kalikajang, Kelurahan Gebang, Kecamatan Sidoarjo, Kabupaten Sidoarjo.Metode: Jenis penelitian adalah observasional dengan desain cross sectional. Populasi pada penelitian ini yaitu seluruh rumah tangga yang berada di wilayah Dusun Kalikajang Kelurahan Gebang. Teknik penentuan sample menggunakan simple random sampling dengan rumus dari Lemeshow dan didapatkan 52 responden. Data Primer dikumpulkan dengan wawancara dengan kuesioner. Analisis data menggunakan uji statistik Chi Square untuk menguji hubungan antar variabel bebas dan variabel dependen, dan uji regresi logistik untuk menguji adakah hubungan seluruh variabel bebas dengan variabel terikat.Hasil: Hasil penelitian menunjukkan dari delapan variabel independen yang diujikan, terdapat satu variabel yang berhubungan positif dengan tingkat ketahanan pangan rumah tangga, yaitu pendapatan rumah tangga (p-value<0.001).Kesimpulan: Terdapat hubungan yang bermakna antara tingkat pendapatan dengan status ketahanan pangan rumah tangga di wilayah pesisir di Kecamatan Sidoarjo.